Diffusion MRI analysis of TMS effects on cognitive pain processing and descending pain modulation in chronic knee osteoarthritis - Wang, Max C. (2025)
It is increasingly recognized that chronic pain is characterized by abnormalities in the neural circuits that process the pain signal. The anterior insula (AI) and anterior cingulate cortex (ACC) are two key hubs of high-level attentional processing that have been observed to be altered in chronic pain. Furthermore, the descending pain modulation system (DPMS) that exerts top-down control over afferent nociceptive signals can exhibit maladaptive dynamics in chronic pain. Transcranial magnetic stimulation (TMS) has been proposed as a non-invasive therapy for inducing normalization of aberrant brain circuits. A randomized sham-controlled clinical trial (BoostCPM) was conducted to evaluate the efficacy of an accelerated TMS protocol for treating chronic pain in a cohort of patients with knee osteoarthritis. Diffusion MRI (dMRI) was collected at baseline and after TMS treatment to assess for neuroplastic changes in key pain processing centers.